2010
DOI: 10.1109/tuffc.2010.1716
|View full text |Cite
|
Sign up to set email alerts
|

Parametric imaging for characterizing focal liver lesions in contrast-enhanced ultrasound

Abstract: The differentiation between benign and malignant focal liver lesions plays an important role in diagnosis of liver disease and therapeutic planning of local or general disease. This differentiation, based on characterization, relies on the observation of the dynamic vascular patterns (DVP) of lesions with respect to adjacent parenchyma, and may be assessed during contrast-enhanced ultrasound imaging after a bolus injection. For instance, hemangiomas (i.e., benign lesions) exhibit hyper-enhanced signatures over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 21 publications
1
64
0
Order By: Relevance
“…can be derived. One can process the images pixel by pixel in this way and generate a map for each of the indices [13,14]. It should be noted that amplitude-derived features are more likely to be affected by system changes than temporally derived features.…”
Section: Contrast-specific Images and Time-intensity Curvesmentioning
confidence: 99%
“…can be derived. One can process the images pixel by pixel in this way and generate a map for each of the indices [13,14]. It should be noted that amplitude-derived features are more likely to be affected by system changes than temporally derived features.…”
Section: Contrast-specific Images and Time-intensity Curvesmentioning
confidence: 99%
“…19,20 Previous P Â P based reports handled the problem of noise by either discarding misbehaving pixels, 34 fitting their data to simple mathematical models, 24,25 or by employing variables that were relatively insensitive to fluctuations within the signal. 27 In this report, noise was handled by two key preprocessing steps: (1) optimal selection of the reference frame independently for each video for accurate motion correction and (2) using noise filters optimized for each parameter.…”
Section: Image Analysismentioning
confidence: 99%
“…These observations were similar to those of Rognin et al where malignant focal liver lesions were found to initially hyperenhance prior to becoming hypoenhanced in the later portal-venous phase. 27 However, Zhao et al found that contrast medium persisted in the late phase in malignant human breast tumors and washed out in benign tumors. 42 Although the animal model employed here was a breast tumor model, the characteristic enhancement pattern did not match that of its human counterpart.…”
Section: B Classification Optimization With the Fisher Discriminant mentioning
confidence: 99%
See 2 more Smart Citations